Proceedings of the Workshop on Promoting Harmonized Policies and Procedures for Quality Seed Production and Trade in Eastern Africa - Eastern and Central Africa Programme for Policy Analysis (ECAPAPA, 2004)
This workshop was a step further, after an executive members committee meeting of the national seed trade associations in Eastern Africa which was convened by ASARECA-ECAPAPA from 25-26 September 2003 in Arusha, Tanzania